Feedbacks between hydrodynamics and cold-water coral mound development. (December 2021) - van der Kaaden, Anna-Selma; Mohn, Christian; Gerkema, Theo; Maier, Sandra R.; de Froe, Evert; van de Koppel, Johan; Rietkerk, Max; Soetaert, Karline; van Oevelen, Dick
Abstract: Cold-water corals rely on currents to transport food towards them and when external conditions are favourable, they can form coral mounds. These structures, which can be over 300 m high, influence the hydrodynamics around the reefs that grow on the mounds, which feeds back to affect coral- and therefore mound-growth. We investigated these feedbacks at the Logachev coral mound province, by running simulations with a 3D hydrodynamic model (Roms-Agrif), using different seafloor bathymetries that represent consecutive stages of mound development. Simulations ranged from a fully smoothened bathymetry without mounds, to a coral mound (Haas mound) at 1.5 times its current size. The effect of mound height on coral growth was investigated by looking at the baroclinic (internal) tide, turbulent energy dissipation, vertical velocities, and horizontal bottom currents. The simulations suggest that with increasing mound height horizontal velocities increase, while turbulent energy dissipation and vertical velocities around the mound foot decrease. This supposedly limits coral growth at the mound foot and hence lateral mound extension in later stages of development. An increase in turbulent energy dissipation and vertical velocities on the mound top and upper flanks, indicates vertical mound growth at all subsequent stages. Our findings of continued vertical mound growth provide an explanation for recently published data on benthic cover from a transect over Haas mound, that show a dominance of live corals on the mound top. We find areas of increased energy conversion rates from the barotropic (surface) to the baroclinic tide on the bathymetry where we artificially eliminated the mounds from (i.e. smoothened bathymetry). Interestingly, these areas overlap with the region where coral mounds are located at present. So, the baroclinic tide is likely an important mechanism in the process of coral mound establishment. Given the relative ease with which the energy conversion rate from the barotropic to the baroclinic tide can be deduced from hydrodynamic model simulations, our results provide opportunities to investigate where coral mounds may be initiated worldwide. Graphical abstract: Image 1 Highlights: We simulated hydrodynamics around different stages of coral mound development. Simulations were analysed for benthic food supply proxies, e.g. vertical mixing. Trapped baroclinic (internal) tides seem to be related to coral mound initiation. Mounds affect benthic-pelagic coupling already when they are tens of meters tall. Vertical food supply increases with mound height, with no limiting feedbacks.